IMPROVING STUDENTS’ LEARNING OUTCOMES THROUGH COOPERATIVE LEARNING MODEL OF GAME METHOD IN CIVICS LEARNING AT GRADE VI SD 005 KUMPAI - Masran (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This research was initiated by the low ability of students at grade VI SDN 005 Pulau Kumpai. The minimum achievement criteria (KKM) for PKN subjet was 65. Unfortunately, only 2 students, out of 10 students at grade VI, scored above the KKM while the other 8 students scored below the KKM. This research was a classroom action research (CAR) which aimed to improve the Civics learning outcomes in reading and understanding texts of students at grade VI SDN 005 Pulau Kumpai through cooperative learning model of game method. The subjects of this research were 10 students at SDN 005 Pulau Kumpai, consisting of 2 boys and 8 girls. This research was conducted in two cycles; each cycle consisted of four stages: planning, implementing, observing, and reflecting. The learning process was conducted through the game method of cooperative learning. The results of this research obtained that the initial score before the action was 61.50 and it increased in the first cycle I by 2.5% with an average of 64.00. then, in the second cycle, the score increased by 7.5% from the basic score with an average of 71.50. Before starting the treatment, 80% of the total number of students (8 students) did not achieved the minimum achievement criteria (KKM) while 2 students achieved the KKM. In cycle I, 6 students could not achieve the KKM and 4 students already achieved the KKM. Moreover, in cycle 2, there was only 1 student who could not reach the KKM and almost all students (9 students) already reached the KKM. Based on the results, it could be concluded that cooperative learning model of game method improved the students’ learning outcomes in Civics learning at grade VI SDN 005 Pulau Kumpai especially in reading and understanding the content of reading materials